A facile naphthalene-based fluorescent chemodosimeter for mercury ions in aqueous solution. Issue 22 (6th February 2015) - Han, Yifeng; Yang, Chengyu; Wu, Kai; Chen, Yu; Zhou, Baocheng; Xia, Min
Abstract : A facile naphthalene-based fluorescence "turn-on" chemodosimeter for rapid, selective and sensitive detection of Hg 2+ by mercury-promoted hydrolysis of the vinylether group has been reported. Abstract : A facile naphthalene-based fluorescence "turn-on" chemodosimeter, 2-((2-(vinyloxy)naphthalen-1-yl)methylene)-malononitrile (MS1 ), for rapid, selective and sensitive detection of Hg 2+ by mercury-promoted hydrolysis of the vinylether group has been reported. The probe displayed a fast response time, and a sensitive fluorescence response (100-fold fluorescence enhancement) to the detection of Hg 2+ in aqueous solution.